2012
DOI: 10.5505/abantmedj.2012.46229
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness And Complications of Transobturator Tape Operation: Analysis of 120 cases

Abstract: Amaç: Bu çalışmanın amacı; minimal-invazif bir teknik olarak tanımlanan transobturator tape (TOT) operasyonunun etkinliğinin ve komplikasyonlarının değerlendirilmesidir. Yöntemler: 2011-2012 yılları arasında saf stres üriner inkontinans (SÜİ) veya mikst üriner inkontinans (MÜİ) nedeniyle subüretral gergisiz vajinal TOT operasyonu yapılan 120 hasta çalışmaya alındı. Tüm operasyonlar dıştan-içe Obtryx™ (Boston Scientific, Natick, MA, USA) marka kit ile gerçekleştirildi. Hastalar postoperatif 1. ve 3. aylarda kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…De novo urge incontinence effects the life quality negatively and de novo urge incontinence rate was low (4,2 %) in the TOT group in the study of Afflar et al and this rate was similar with the literature (12,16,17) .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…De novo urge incontinence effects the life quality negatively and de novo urge incontinence rate was low (4,2 %) in the TOT group in the study of Afflar et al and this rate was similar with the literature (12,16,17) .…”
Section: Discussionsupporting
confidence: 77%
“…None of the cases in the mini sling group developed hemorrhage over 200 ml. Afflar et al reported that only one patient required transfusion and haematoma didn't occur in this case (12) . They reported the rate of hemorrhage over 200 ml as 3,3 % and this rate overlaps Early complications of the transobturator tape and mini sling procedure with the findings of Abdel-Fattah et.al (13) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Though it is a minimally invasive method, complications such as vaginal perforation, de novo incontinence, perineal pain, and vaginal erosion can be seen. [3] Bladder injuries is one of the rarely reported challenging complications that might occur after TOT. [4] Case presentation Our case presentation was written after approval of the patient was obtained.…”
Section: Introductionmentioning
confidence: 99%